Agricultural extension for rural development: issue and challenges - Shantanu Kumar; Sah, Uma (2002)
To meet the challenges of agricultural development in this millennium, there is an urgent need to redefine the structure and functions of Agricultural Extension. Also, to make the Agricultural Extension more viable and efficient tool of technology transfer, several issues must be addressed so that it can be further meaningful to accommodate with the changing scenario of agricultural research and development in the years to come. In the present article, authors have reviewed some of those issues that could be the important determinants for the success of Agricultural Extension in this millennium. - Reproduced.
Keywords: Rural extension; Rural development